BUSINESS FEASIBILITY ANALYSIS OF THE MSMES “SEBLAK KING” - Yurofi’ah, Ilma Alfi; Luluk Fauziah (PT. Antis International Publisher, 2025)
Objective: Indonesia is one of the countries that is a tourist destination because of its culinary richness. The potential for a strong national economic base can be seen from the very large number of MSMEs and their ability to absorb a large workforce. MSME